2012
DOI: 10.1055/s-0031-1283885
|View full text |Cite
|
Sign up to set email alerts
|

Was leisten Risiko-Scores beim rupturierten abdominellen Aortenaneurysma (rAAA)?

Abstract: This study revealed clear differences in the prognostic predictions of the various scores. In accord with the literature, no score gave a 100 % positive result with regard to mortality. Thus, an individual decision or, respectively, a therapeutic option cannot be reached with the help of the investigated scores. Further parameters need to be evaluated in order to make decisions about postoperative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Univariate studies have revealed a small number of risk factors associated with death after rAAA repair, which, in turn, have been incorporated into riskscoring systems. No fewer than 18 risk scores and subsequent modifications have been evaluated for their usefulness in assessing individual risk (28). The published findings are inconsistent; in any case, no score seems capable of predicting the fate of an individual patient reliably enough to permit therapeutic decision-making on the basis of the score alone.…”
Section: Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Univariate studies have revealed a small number of risk factors associated with death after rAAA repair, which, in turn, have been incorporated into riskscoring systems. No fewer than 18 risk scores and subsequent modifications have been evaluated for their usefulness in assessing individual risk (28). The published findings are inconsistent; in any case, no score seems capable of predicting the fate of an individual patient reliably enough to permit therapeutic decision-making on the basis of the score alone.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The published findings are inconsistent; in any case, no score seems capable of predicting the fate of an individual patient reliably enough to permit therapeutic decision-making on the basis of the score alone. Some scores do, however, seem to be useful for comparing groups of patients in different treatment centers and for comparing the results of different types of treatment (28).…”
Section: Risk Assessmentmentioning
confidence: 99%